Psychosocial Adjustment in Ugandan Children: Coping With Human Immunodeficiency Virus Exposure, Lifetime Adversity, and Importance of Social Support - Tuke, Robert; Sikorskii, Alla; Zalwango, Sarah K.; Webster, Kyle D.; Ismail, Alexander; Pobee, Ruth A.; Barkin, Jennifer L.; Boivin, Michael J.; Giordani, Bruno; Ezeamama, Amara E. (New Directions for Child and Adolescent Development, 2020)
Cumulative lifetime adversity and social support were investigated as determinants of psychosocial adjustment (esteem, distress, hopefulness, positive outlook/ future aspirations, and sense of purpose) over 12months in 6–10-years-old HIV-infected, HIV-exposed uninfected and HIV-unexposed uninfected children from Uganda. Each determinant and psychosocial adjustment indicator was self-reported using standardized questionnaires administered at baseline, 6, and 12 months. Linear mixed effects models were used to relate time-varying lifetime adversity and social support to psychosocial adjustment over 12 months. Regardless of HIV status, higher adversity predicted lower esteem (coefficient b = −2.98, 95% confidence interval (CI): [−4.62, −1.35]) and increased distress (b =3.96, 95% CI: [1.29, 6.62]) but was not associated with hopefulness, positive outlook or sense of purpose. Low social support predicted higher distress (b =9.05, 95% CI: [7.36, 10.73]), lower positive outlook
Keywords: Psychosocial Adjustment; Children; Human Immunodeficiency Virus; Lifetime Adversity; Social Support